Serum gamma glutamyltransferase as a marker of metabolic syndrome and coronary disease likelihood in nondiabetic middle-aged and elderly adults - Onat, Altan; Hergenc, Gulay; Karabulut, Ahmet; Turkmen, Serdar; Dogan, Yuksel; Uyarel, Huseyin; Can, Gunay; Sansoy, Vedat (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2006)
The role of serum gamma glutamyltransferase (GGT) activity as a cardiovascular risk marker was studied basically cross-sectionally. After appropriate exclusions, 754 men and 802 women were available for analysis who were followed up briefly yielding only 16% of overall cases of coronary heart disease (CHD). GGT activity was measured kinetically. In multivariate analysis across 12 variables, waist circumference, sex, complement C3, moderate alcohol intake and uric acid were significant independent covariates of serum GGT. By analyzing the sample in tertiles, doubling in GGT activity was found associated with a rise of 74% in metabolic syndrome (MS) likelihood-independent of salient confounders (P < 0.001). This association was mediated by waist circumference. Individuals in the top versus the bottom tertile exhibited an odds ratio for CHD likelihood of 1.81 (95% CI 1.09; 3.02)-independent of age, sex, total cholesterol, systolic blood pressure, impaired fasting glucose, smoking status, alcohol usage and, notably, of waist circumference. This indicated that a doubling in serum GGT activity corresponded to a 45% excess in CHD likelihood, after adjustment for standard risk factors. In conclusion, waist circumference is a major determinant of serum GGT activity among Turkish adults. Doubling in activity is associated with a (largely waist girth mediated) rise by over one-half in the multiadjusted MS likelihood, and by nearly one-half in the CHD likelihood, independent of waist girth and major risk factors. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: cardiovascular risk factors; coronary heart disease; gamma glutamyltransferase; metabolic syndrome; population-based study; risk assessment; GLUTAMYL-TRANSFERASE; CARDIOVASCULAR-DISEASE; RISK; ASSOCIATION; MORTALITY; Public, Environmental & Occupational Health; General & Internal Medicine